Przestrzenne zróżnicowanie gmin wiejskich w województwie świętokrzyskim ze względu na poziom zrównoważenia rozwoju - Popławski, Łukasz; Wojewodzic, Tomasz (Spatial Differentiation of Rural Communes in Świętokrzyskie Voivodeship in Terms of the Level of Development Sustainability, 2009)
Świętokrzyskie voivodeship is a region including the Holy Cross Mountains, having an area of 2776 km2 and a population of 228 thousand. The Świętokrzyskie voivodeship is very interesting owing to its beautiful landscape and a lot of interesting monuments. The natural resources of this region are forests and mineral resources. In this region there are also numerous monuments of Polish history and culture. These values determine its protective, scientific, tourist and didactic functions. The basis of planning sustainable development is spatial research, as a result of which one can distinguish the groups of similar units and valorize the state of their development. The work presents the suggestions of a procedure employed for the identification of territorial units showing considerable disproportions between economic development and the quality of the environment. For the estimation of economic development and environment qualities, five diagnostic features have been chosen, which, according to the authors, described the studied phenomena in the best possible way and at the same time their quantification was possible in all territorial units undergoing the analysis. The assessment is relative in character, since one can find there the comparison between parameters describing the investigated phenomena in relation to units characterized by extreme values of investigated features. In the conducted research the method of zero unitarization is applied. As a result of the research the communes of Świętokrzyskie voivodeship are divided into: communes with sustainable development of the environment, communes with unsustainable development of the environment, communes economically underdeveloped and communes where economic and environment development is neglected
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 60-70